An analysis of translation techniques for racist utterances in Rush Hour 3 - Jonathan Haryana; Muhammad Aprianto Budhie Nugroho; Wulan Rahmatunisa (Concept : Community Concern for English Pedagogy and Teaching, 2024)
This study aims to analyse the translation of racist content in the movie subtitles of "Rush Hour 3" by Dhespy fansub (Movieku) and Putra fansub (Lk21). The research uses a qualitative method and a case study design. Document analysis, including transcripts and subtitles, was employed in this research. The data were analysed by using the theory from Molina and Albir (2002). The result shows that 86 data were taken from the 2 fansub translators (43 data for each). Based on findings, there are 14 types of translation techniques are used, namely; Adaptation, Amplification, Borrowing, Calque, Compensation, Description, Establish Equivalent, Generalization, Linguistic Amplification, Linguistic Compression, Literal Translation, Modulation, Particularization, and Reduction. The researchers found that both fansubs used multiple translation techniques, with single (38%), duplet (40%), triplet (20%), and quartet groups (2%). In the Dhespy group, single grouping occurred 16 times (37%), duplet 15 times (35%), triplet 10 times (23%), and quartet 2 times (5%). In the fansub group, single grouping occurred 17 times (40%), duplet 19 times (44%), triplet 7 times (16%), and quartet none. The researchers hope this research can be helpful as a reference for readers who want to add knowledge about language features to their study. Keywords: Movie; Racism; Translation Technique; Translator